The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.21203/rs.3.rs-2429085/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of Tax Digitalisation on Tax Revenues in Sub-Saharan Africa: A Systematic Review

Abstract: This study investigates whether and how tax digitalisation reforms operated in sub-Saharan African countries generate more tax revenues. To this end, we performed a systematic literature review based on case-country studies. Our conceptual model shows that new business creation, tax morale, tax compliance, efficiency in tax collection and e-governance are channels through which the digital economy affects the mobilisation of tax revenues. We also found that tax digitalisation significantly improved tax revenue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, since audits are costly for tax authorities, it is not possible to systematically audit all taxpayers. Bassongui and Houngbédji (2021) also developed a conceptual model of the tax-digitalization nexus and showed that digitalization improves tax efforts through three main channels. First, digitalization improves the tax base and tax compliance by giving better information to tax authorities on the identification of individuals and economic activities such as bank transactions and interest income.…”
Section: Methodsmentioning
confidence: 99%
“…However, since audits are costly for tax authorities, it is not possible to systematically audit all taxpayers. Bassongui and Houngbédji (2021) also developed a conceptual model of the tax-digitalization nexus and showed that digitalization improves tax efforts through three main channels. First, digitalization improves the tax base and tax compliance by giving better information to tax authorities on the identification of individuals and economic activities such as bank transactions and interest income.…”
Section: Methodsmentioning
confidence: 99%
“…They emphasized the need for taxpayers and tax authorities to devise strategies to address taxation issues arising from transactions in the digital economy. Additionally, Bassongui & Houngbédji (2023) presented a conceptual model illustrating the impact of tax digitalization on tax revenues in Sub-Saharan Africa, emphasizing the channels through which the digital economy affects tax revenues. This underscores the importance of understanding the implications of digitalization on tax compliance and revenue mobilization.…”
Section: Future Trends and Policy Implicationsmentioning
confidence: 99%
“…This is in response to the shifting behavior of individuals increasingly relying on digital platforms. Bassongui and Houngbédji (2023) demonstrates that digitizing taxes might lead to a substantial rise in revenue from taxes.…”
Section: Introductionmentioning
confidence: 99%